2021
DOI: 10.1542/peds.2021-053418
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe COVID-19 in Children

Abstract: report receiving funding from the CDC EIP cooperative agreement. Libby Reeg and Laurie Billing report receiving a CDC federal grant from the Council of State and Territorial Epidemiologists. Laurie Billing reports receiving Epidemiology and Laboratory Capacity (ELC) grant funding from CDC to support vaccine preventable disease epidemiology staffing and additionally report receiving Immunizations and Vaccines for Children (VFC) grant funding from CDC. Evan Anderson has consulted for Pfizer, Sanofi Pasteur, Jans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
172
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(216 citation statements)
references
References 31 publications
12
172
5
3
Order By: Relevance
“…Five of the six hospitals had policies to test all pediatric patients for SARS-CoV-2 upon admission during the study period, allowing for detection of incidental positive SARS-CoV-2 test results. However, the proportion of such patients was smaller in this study compared with that in a previous report (1). Patients aged 0-4 and 12-17 years accounted for 79% of COVID-19-related hospitalizations in this study, which is consistent with data from other hospitals and communities (2).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Five of the six hospitals had policies to test all pediatric patients for SARS-CoV-2 upon admission during the study period, allowing for detection of incidental positive SARS-CoV-2 test results. However, the proportion of such patients was smaller in this study compared with that in a previous report (1). Patients aged 0-4 and 12-17 years accounted for 79% of COVID-19-related hospitalizations in this study, which is consistent with data from other hospitals and communities (2).…”
Section: Discussionsupporting
confidence: 86%
“…Black or Hispanic in this study; an earlier study demonstrated higher hospitalization rates among Black or Hispanic children compared with White children (1). Approximately two thirds of patients hospitalized for COVID-19, including 83% and 88% of patients aged 5-11 and 12-17 years, respectively, had one or more underlying medical conditions.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Despite the high level of protection afforded by vaccination 2 and the documented severity of Covid-19 in adolescents, 26 only 39% of the controls in our study were fully vaccinated against Covid-19. These data suggest that efforts to improve vaccination coverage among all adolescents, especially those at highest risk for severe Covid-19, 28 , 29 could markedly decrease the risk of severe Covid-19 among adolescents in the United States.…”
Section: Discussionmentioning
confidence: 87%
“…Because of the large number of cases during December 2021, some sites examined clinical outcome data on a representative sample of hospitalized children. † † † Data on indicators of severe disease were collected (i.e., hospital length of stay, ICU admission, use of invasive mechanical ventilation [IMV], § § § and in-hospital death), as were data on primary reason for admission ¶ ¶ ¶ and symptoms that were present when the patient was admitted**** (3). Proportions were compared between periods of Delta predominance (July 1-December 18, 2021) and Omicron predominance (December 19-31, 2021); a variant that accounted for >50% of sequenced isolates was considered to be predominant.…”
mentioning
confidence: 99%